2017
DOI: 10.18632/oncotarget.23593
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SOX21-AS1 modulates breast cancer stem cells properties and carcinogenesis via targeting SOX2

Abstract: Breast cancer stem cells (CSCs) are important element in the tumorigenesis and relapse. Long non-coding RNAs (lncRNAs) had been proved to regulate the breast cancer carcinogenesis. In present study, our research team aims to investigate the deepgoing role of SOX21-AS1 on breast CSCs properties and carcinogenesis. Human lncRNA microarray analysis and RT-PCR showed that SOX21-AS1 was up-regulated in breast cancer tissue. Moreover, the overexpression of SOX21-AS1 indicated the poor prognosis of breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Remarkably, SOX21-AS1 knockdown was shown to reduce proliferation, invasion, tumor growth, stem factor expression of the CD44 + /CD24 − population in vitro and in vivo. This investigation suggests that SOX21-AS1 controls bCSC properties and carcinogenesis via targeting Sox2 [ 148 ]. Posteriorly, it was corroborated that the lncRNA SOX21-AS1 is highly expressed in bCSCs of MCF-7 and MDA-MB-231, promoting bCSC properties as well as the proliferation, migration, and invasion abilities of CSC-MCF-7 cells through inhibiting the Hippo signaling pathway [ 149 ].…”
Section: The Lncrna: Key Molecules In the Breast Cancer Stem Cellsmentioning
confidence: 99%
“…Remarkably, SOX21-AS1 knockdown was shown to reduce proliferation, invasion, tumor growth, stem factor expression of the CD44 + /CD24 − population in vitro and in vivo. This investigation suggests that SOX21-AS1 controls bCSC properties and carcinogenesis via targeting Sox2 [ 148 ]. Posteriorly, it was corroborated that the lncRNA SOX21-AS1 is highly expressed in bCSCs of MCF-7 and MDA-MB-231, promoting bCSC properties as well as the proliferation, migration, and invasion abilities of CSC-MCF-7 cells through inhibiting the Hippo signaling pathway [ 149 ].…”
Section: The Lncrna: Key Molecules In the Breast Cancer Stem Cellsmentioning
confidence: 99%
“…Notably, SOX21-AS1 knockdown was proven to diminish proliferation, invasion and stem factor, i.e., Nanog, LIN28, Oct4 and SOX2, of BCSCs. This study indicates that SOX21-AS1 regulates properties and carcinogenesis of BCSC via targeting SOX2 [ 117 ]. It was further confirmed that the lncRNA SOX21-AS1 is overexpressed in BCSCs of MCF-7 and MDA-MB-231, enhancing stemness of BCSC as well as proliferation, invasion and migration in CSC-MCF-7 cells via suppressing the Hippo signaling pathway [ 118 ].…”
Section: Epigenetic Regulation In Breast Cancer and Bcscsmentioning
confidence: 99%
“…Recent studies have shown that lncRNA SOX21-AS1 is located at chromosome 13q32.1 and transcribed into a 2986 nucleotide transcript, which exerts important functions in tumorigenesis and maintenance of tumor stem cell characteristics [9]. For example, SOX21-AS1 modulates breast cancer stem cells properties and carcinogenesis via targeting SOX2 [10]. Although there is evidence that SOX21-AS1 is involved in the proliferation, invasion and maintenance of the stemness of BCSCs [10][11][12], the underlying molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SOX21-AS1 modulates breast cancer stem cells properties and carcinogenesis via targeting SOX2 [10]. Although there is evidence that SOX21-AS1 is involved in the proliferation, invasion and maintenance of the stemness of BCSCs [10][11][12], the underlying molecular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%